AN ANALYSIS OF FACTORS INFLUENCING PUBLIC INTEREST IN INVESTING IN THE SHARIA CAPITAL MARKET: EVIDENCE FROM THE UISI INVESTMENT GALLERY - Malik, Ahmad Dahlan (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2017)
In an effort to grow the country's economy after the global financial crisis, and to support government policies, investors are needed to play their part through the capital market. As the capital market developed to reduce uncertainty and play a role in the real economy, the Islamic capital market was formed with the aim of accommodating both Muslim and non-Muslim investors. In order to develop investors' roles in the Islamic capital market, it is necessary to analyze investors so that they are interested in investing their capital in the Islamic capital market. To achieve this goal, this study was conducted by analyzing the factors that influence investor interest through the UISI investment gallery exchange, namely risk factors, income level, motivation, knowledge, perception, and learning to invest in the Islamic capital market. The results of the study produced the model Y = 0.011 + 0.386 X1 + 0.380 X2 + 0.290 X3 – 0.016 X4 – 0.045 X5 – 0.005 X6. From this model, the significant roles are played by the variables of risk, income, and motivation, which are important to consider for respondents or investors in BGIU (UISI Investment Gallery Exchange) compared to others because these variables have a positive regression.